“De que cor eu sou?” O lugar da menina negra no espaço escolar – um estudo sobre a representação das Mulheres Negras no livro didático de história - MIRANDA, Caroline Barroso (Universidade Federal do Pará, 2023)
This thesis aims to reflect on the concepts of black feminist thought, the school History knowledge, the History of black women and their representations in images in the History textbooks of the 8th year of fundamental education (or brazilian middle school). Using as source of research and reflection the History textbook and its black female students narrative so that it is possible to understand how the representations of black women in these textbooks occur between the years 2001 to 2017 and how the black female students see themselves represented in the History textbook, in History teaching and in society. It also seeks to understand how the intersectionalized structures of race, gender and class influence the ruptures and permanences, characteristics of the historical process, and the imagery representations of black women in textbooks. Understanding how racism, sexism and classism in Brazil affect the historical narrative in the representation of black women in History textbooks, analyzing how these women have gained ground and visibility in the production of textbooks over the years. Also it seeks to promote social justice through the History teaching-learning process and from the specific standpoint of black female students, their place of speech, their self-definitions and empowerment as future black women.